Parallel Integrity and the Problem of Compartmentalization - Gałecki, Sebastian (Roczniki Filozoficzne, 2025)
In recent decades, we have noticed quite an interesting trend in which analyses in the field of general ethics are gradually giving way to the so-called professional or applied ethics. Jarosław Kucharski dealt with the general topic of leaders, little explored in Polish literature. In his book and the article that followed, he advances the most important and controversial thesis that we can demand from a leader only a parallel integrity. This means that someone is a morally good leader if he or she tries to achieve the goals and values related to the leader’s function, regardless of their conduct in other spheres of life. In my article, I try to show that such an approach is in keeping with the modern problem of a complete break-down of the person into separate social roles that he performs.